A Rare Case of a Giant Retroperitoneal Gastrointestinal Stromal Tumor of Malignant Potential - Abdullah M. Alshamrani; Meshare A Albattah; Rasha A Bssas; Fatemah Y Alhedaithy; Mshaeel H Almutairi; Mohayad A Bkheite; Salih H Albishri (International Journal of Innovative Research in Medical Science, 2021)
Gastrointestinal stromal tumors (GIST) are mesenchymal tumors that originate in the gastrointestinal tract. We present the case of a 30-year-old man who presented with progressive abdominal distension of one-years’ duration. A physical examination revealed a distended, tense, non-tender abdomen, and initial imaging investigations revealed a huge cystic, septate abdominal mass. A provisional diagnosis was made of a huge retroperitoneal, malignant, cystic mass. However, aspiration cytology showed signs suggestive of a benign cyst. Cystic tumor excision performed with control of drain site to prevent leakeage throughout the procedure. The tumor extending into the pelvis, measuring approximately 17 x 31 x 42 cm in diameter and weighing 3.78 kg. The tumor was resected, and a histopathological examination showed findings consistent with a GIST of mixed spindle and epithelioid type. Further evaluations revealed that the tumor was positive for CD 117 and CD 34, prompting the oncology team to start the patient on oral imatinib 400 mg once daily. No evidence of local recurrence or distant metastasis was noted on an abdominal computed tomography scan performed during the follow-up visit up to October 2020 last follow-up. The clinical presentation of GISTs is often complex, making its diagnosis challenging, especially in patients who present with non-specific gastrointestinal symptoms. The successful management of these tumors requires a multidisciplinary approach, and regular follow-ups.